2020
DOI: 10.3390/w12102671
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Background Values of Selected Chemical Substances in Four Groundwater Bodies in the Pannonian Region of Croatia

Abstract: Groundwater quality is a consequence of cumulative effects of natural and anthropogenic processes occurring in unsaturated and saturated zone, which, in certain conditions, can lead to elevated concentrations of chemical substances in groundwater. In this paper, the concept of determining the ambient background value of a chemical substance in groundwater was applied, because the long-term effects of human activity influence the increase in concentrations of substances in the environment. The upper limits of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…Nitrogen may be present in soil and water mains in four forms (gaseous nitrogen, organic nitrogen, ammonium ion, and nitrates), and it can be introduced into the environment by inorganic fertilizers, human and animal waste, etc. The concentrations of nitrates in Mediterranean waters oscillate between 4 to 496 mg L −1 in MENA Countries and between 3.23 to 50.1 mg L −1 in European Countries [31][32][33]. Balestrini et al (2021) have shown that the increase in nitrate pollution in Mediterranean Countries is often related to the increase in livestock and intensive agriculture, given that the nitrates come from synthetic fertilizers [32].…”
Section: (I) Chemical and Biological Water Pollutionmentioning
confidence: 99%
“…Nitrogen may be present in soil and water mains in four forms (gaseous nitrogen, organic nitrogen, ammonium ion, and nitrates), and it can be introduced into the environment by inorganic fertilizers, human and animal waste, etc. The concentrations of nitrates in Mediterranean waters oscillate between 4 to 496 mg L −1 in MENA Countries and between 3.23 to 50.1 mg L −1 in European Countries [31][32][33]. Balestrini et al (2021) have shown that the increase in nitrate pollution in Mediterranean Countries is often related to the increase in livestock and intensive agriculture, given that the nitrates come from synthetic fertilizers [32].…”
Section: (I) Chemical and Biological Water Pollutionmentioning
confidence: 99%
“…The samples exceeding a fixed value of the chosen markers are eliminated and the NBL is chosen as the 90th, 95th, or 97.7th percentile of the remaining water samples dataset. The main disadvantage of this approach is that the samples are eliminated according to qualitative criteria [17], e. g. the amount of available data and the shape of the related statistical distribution, and that the removal of samples might result in a too scarce data set.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this Special Issue of Water is to bring together and discuss different methodological approaches and tools to improve the assessment of groundwater NBLs. From its first announcement, and after being thoroughly peer reviewed, nine papers have been accepted for publication [3][4][5][6][7][8][9][10][11]. To provide an overview of the experiences collected by this Special Issue, a brief summary of each published paper is reported below.…”
mentioning
confidence: 99%
“…To provide an overview of the experiences collected by this Special Issue, a brief summary of each published paper is reported below. A variety of spatial scales is encountered, ranging between national [3,11], regional [3,7,8,10], meso- [6,9] and site-specific [4,5] scales, and different methodologies are applied.…”
mentioning
confidence: 99%
See 1 more Smart Citation